2008
DOI: 10.2174/187221408786241838
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Search for Biomarkers for the Diagnosis and Monitoring of Diabetes

Abstract: In the fields of genomic, proteomic and metabolomic technologies many advances have been made in the past few years for the early diagnosis and monitoring of diseases such as diabetes mellitus. As diabetes is afflicting affluent and developing societies throughout the world and is fuelled by aging demographics and the recent increase of obesity and related insulin resistance, there is a clear need to discover effective agents for diagnosing the disease and controlling glycaemic status. Biological markers such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus, identification of susceptibility or resistance genes in DN will provide better knowledge of pathomechanism, genetic biomarkers and future therapies. [48][49][50] Considerable studies have indicated that the levels of ADIPOQ are influenced by genetic polymorphisms in the ADIPOQ gene [51][52][53][54] and these polymorphisms have been implicated in DN. [8][9][10][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Nephropathy has been associated with high ADIPOQ levels in T1DM and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of susceptibility or resistance genes in DN will provide better knowledge of pathomechanism, genetic biomarkers and future therapies. [48][49][50] Considerable studies have indicated that the levels of ADIPOQ are influenced by genetic polymorphisms in the ADIPOQ gene [51][52][53][54] and these polymorphisms have been implicated in DN. [8][9][10][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Nephropathy has been associated with high ADIPOQ levels in T1DM and T2DM.…”
Section: Discussionmentioning
confidence: 99%